2012
DOI: 10.1177/1470357212453978
|View full text |Cite
|
Sign up to set email alerts
|

Looking healthy: visualizing mental health and illness online

Abstract: Through a historical case study of the mental health community website HealthyPlace.com , the author applies social semiotics and critical discourse analysis to interrogate the visual discourse surrounding mental health online. Web design transformations over the course of a decade demonstrate how visual imagery conveys a shift from a biomedical discourse focused on illness to a social-therapeutic discourse centered on health and wellness. Ultimately, the author argues that the utilization of faces in stock ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…The absence of visual depictions of bodily malfunction or discomfort on these diabetes Facebook pages reflects trends towards positive representations of illness noted in some existing research (Thompson, 2012). This 'utopian discourse of sickness' (Scalvini, 2010, p. 223), in which social actors representing a condition are presented as 'ordinary' or even desirable through high modality stock images of healthy people, represents the prospect of living happily with diabetes.…”
Section: Figure 4 -Post To the Diabetes Uk Facebook Pagementioning
confidence: 99%
See 2 more Smart Citations
“…The absence of visual depictions of bodily malfunction or discomfort on these diabetes Facebook pages reflects trends towards positive representations of illness noted in some existing research (Thompson, 2012). This 'utopian discourse of sickness' (Scalvini, 2010, p. 223), in which social actors representing a condition are presented as 'ordinary' or even desirable through high modality stock images of healthy people, represents the prospect of living happily with diabetes.…”
Section: Figure 4 -Post To the Diabetes Uk Facebook Pagementioning
confidence: 99%
“…In keeping with the use of stock photographs discussed above, these posts continue the trend of conveying diabetes-related content using images of people who meet the gaze of the viewer face on and appear free from physical illness or medical intervention. In combination with the images discussed above, these photos contribute to the 'virtual synthetic personalisation' (Fairclough, 1992;Thompson, 2012;Thurlow, 2013) of the Facebook pages, in which semiotic resources that communicate social affinity with the reader become a dominant visual resource for representing diabetes-related content. In doing so, these images also offer partial representations of diabetes, eliding any suggestion of physical illness that is referred to in the posts' texts and defining the diabetic individual through iconic images of wellness and sociality (Thompson, 2012).…”
Section: ) Representing the Diabetic Individual As Desirable Despitementioning
confidence: 99%
See 1 more Smart Citation
“…As Thurlow (2013) notes, such Pages depend upon the deliberate blurring of boundaries between private practices of social interaction and help-seeking and commercial practices of advertising and marketing such that corporate goals are realised through the personalised discourse that characterises Facebook (Papacharissi, 2009). Strategically employing features of informal, social talk allows these organisations to stylise corporate messages in the form of personalised interactions between friends and thereby broaden their audience appeal (Thompson, 2012). By studying such institutional Facebook Pages, we therefore aim to extend research on online health information by Seale, who calls for a critical approach to online health discourse that 'may shed light on the relations of production that lead to particular [health] representations becoming prominent '(2005: 540).…”
Section: Introduction and Research Questionsmentioning
confidence: 99%
“…According to that reports, the respondents found that doctors have different information from what they got from online media. Moreover, recently, internet has become a notable resource for people to seek health information worldwide (Fox, 2010;Fox and Jones, 2009;Lewis, 2006;Mager, 2009;Wyatt et al, 2005in Thomson, 2012. Thomson (2012) stated, "transformation in digital technology have allowed web designers to bring together visual, textual, and audio forms to communicate messages quite differently to the modern day internet audience."…”
Section: Introductionmentioning
confidence: 99%